2019
DOI: 10.1111/1468-0009.12406
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety Issues Continue to Plague American Hospitals

Abstract: here has been a significant focus on patient safety issues over the past two decades. This began with the release of To Err is Human in late 1999, 1 but has included numerous other reports indicating the substantial number of deaths and injuries due to medical errors. Despite the focus on this topic by hospital associations, medical groups, and various professional organizations, such as the ECRI Institute, a recent report indicates serious challenges remain. 2 Johns Hopkins researchers recently published a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…For example, we repeatedly ask patients to state their name and birth date, take time out to verify procedures, and obsessively clean equipment. Yet, despite these precautions, estimates of preventable hospital deaths range from 22,000 to 160,000 per year 10,11…”
Section: Why This Mattersmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, we repeatedly ask patients to state their name and birth date, take time out to verify procedures, and obsessively clean equipment. Yet, despite these precautions, estimates of preventable hospital deaths range from 22,000 to 160,000 per year 10,11…”
Section: Why This Mattersmentioning
confidence: 99%
“…Yet, despite these precautions, estimates of preventable hospital deaths range from 22,000 to 160,000 per year. 10,11 Though more research is needed, it's possible that a number of these deaths resulted from caregivers struggling with the negative emotions cited in the Gallup study. In his seminal study on the psychology of military incompetence, Norman Dixon concluded that the primary distinction between competent and incompetent commanders was their ability, or inability, to manage anxiety.…”
Section: Why This Mattersmentioning
confidence: 99%